(untitled) (Journal of the College of Basic Education, 2024)
Throughout the ages, the book of God remains the immortal constitution of humanity, including divine mysteries and endless divine judgments. Knowing this dear book and its indications and purposes and delving into its meanings is the goal of every seeker of knowledge who wants to draw knowledge from its contents. The Qur’an is the miraculous book of God whose wonders never end and its resources never end. God made it a guidance and mercy for people at all times and places. Therefore, the exegetical lesson still occupies a special place and great importance among researchers of science and the study of its sanctity derived from the sanctity of the Holy Qur’an. As recent studies tended to explore its meanings, rulings, and laws, to draw from its inexhaustible wellspring over time, that which attracted commentators in this modern era, and the existence of the necessity of renewal in social interpretation through the bitter reality experienced by the nation, so it was a renaissance for reform at the hands of scholars to interpret those who tended Towards the method, with the intention of advancing the reality of the nation to treat its problems and reform them through the study of social aspects, so I dealt with the interpretation of Diaa Al-Furqan by Mr. Muhammad Taqi Al-Naqwi, where I added it to research and extract the social aspects in the interpretation